Fossil corals as an archive of secular variations in seawater chemistry since the Mesozoic. (1st July 2015) - Gothmann, Anne M.; Stolarski, Jarosław; Adkins, Jess F.; Schoene, Blair; Dennis, Kate J.; Schrag, Daniel P.; Mazur, Maciej; Bender, Michael L.
Abstract: Numerous archives suggest that the major ion and isotopic composition of seawater have changed in parallel with large variations in geologic processes and Earth's climate. However, our understanding of the mechanisms driving secular changes in seawater chemistry on geologic timescales is limited by the resolution of data in time, large uncertainties in seawater chemistry reconstructions, and ambiguities introduced by sample diagenesis. We validated the preservation of a suite of ∼60 unrecrystallized aragonitic fossil scleractinian corals, ranging in age from Triassic through Recent, for use as new archives of past seawater chemistry. Optical and secondary electron microscopy (SEM) studies reveal that fossil coral crystal fabrics are similar to those of modern coralline aragonite. X-ray diffractometry (XRD), cathodoluminescence microscopy (CL), and Raman studies confirm that these specimens contain little to no secondary calcite. In order to screen for geochemical changes indicative of alteration, we measured 87 Sr/ 86 Sr ratios, clumped isotopes, and trace element ratios sensitive to diagenesis (e.g., Mn/Ca). We retain samples when these tests either fail to identify any diagenetic modifications, or identify specific domains free of detectable alteration. Using the validated fossil coral archive we reconstruct seawater Mg/Ca and Sr/Ca ratios, measured by Secondary Ion Mass Spectrometry (SIMS), back to ∼230 Ma. The effects of temperature on coral trace element incorporation cannot explain the trends observed in our fossil coral Mg/Ca and Sr/Ca data. In agreement with independent records, seawater Mg/Ca molar ratios inferred from corals are low (Mg/Ca ∼1) during the Cretaceous and Jurassic, and increase between the Early Cenozoic and present (Mg/Ca = 5.2). Seawater Sr/Ca ratios from corals vary systematically between ∼8 and 13 mmol/mol since 230 Ma, with maximum values in the Cretaceous and Paleogene. The coral Sr/Ca record disagrees with records from hydrothermal CaCO3 veins, but is similar to those reconstructed from other biogenic carbonates, especially benthic foraminifera. The agreement between corals and other archives, for both Sr/Ca and Mg/Ca ratios, further validates our records. In return, fossil coral records improve our understanding of past variations in seawater Mg/Ca and Sr/Ca.